The Singapore Afterlife (1970–2007) of the Japanese Architectural Movement Metabolism (新陳代謝 / Shinchintaisha, 1959–1973) - Novenario, Jose Lorenzo (Silva Iaponicarum, 2024)
This paper employs the art-historical and descriptive-analytical methods to discuss the history of Metabolism in Singapore. Firstly, it discusses the conceptual and philosophical underpinnings of Metabolism with recurring themes of organic and technological terminologies to organize the modern city. It then reviews the current literature on Metabolism, emphasizing the contributions made to the analysis of Metabolism as a philosophy and an architectural movement. The paper then uses as examples the buildings which were designed and built in Singapore by Tange Kenzō and Maki Fumihiko. However, the influence of Metabolism was felt in Singapore even earlier through local architects who were inspired by its principles of designing residential and commercial spaces by means of incorporating modularity, communal living, and green urbanism into the design. Finally, the paper reflects on the influence of Metabolism on current green architecture movements in Singapore.